Empirical Validation of Lunar Timing for Hijama: A Cross-Sectional Study of Hemostatic and Immune Biomarkers from Yemen - Naif Ali; Radfan Saleh Abdullah; Ibrahim Ahmed; Othman Mohammed; Akram Jamal; Fawaz Ahmed; Bushra Dahan; Alawy Adel; Tofaha Abdullah; Mother Saleh; Shadia Hamid; Naif Mohammed; Khawla Mohammed; Yaqoub Khalid; Sabran Nabil; Abdulmajeed Abdulkareem; Abdulkareem Mohammed Abdulkareem; Mohammed Ali (CV Media Inti Teknologi, 2026)
Background: Prophetic Medicine (Al-Tibb al-Nabawi) recommends performing Hijama (wet cupping) on specific mid-lunar days (17th, 19th, and 21st of the Hijri month). This recommendation has lacked empirical validation until now.Objectives: This study aims to empirically validate whether these lunar phases are associated with measurable variations in hemostatic and immunological parameters relevant to Hijama's therapeutic mechanisms.Methods: 258 healthy persons between the ages of 18 and 50 participated in a cross-sectional study conducted in Yemen's Ad'Dla Governorate. Automated systems were used to analyse blood samples taken during the new moon (1st–5th Hijri days) and mid-lunar phase (17th–21st Hijri days) for full blood counts and coagulation profiles. Paired t-tests, two-way ANOVA, bootstrapping, and Bayesian analysis were used to assess the data.Results: Significant improvements in hemostatic and immunological measures, such as higher platelet, monocyte, neutrophil, and eosinophil counts and a shorter clotting time, were linked to the mid-lunar phase (all p < 0.05). ANCOVA verified that these changes were independent of environmental influences (p-phase < 0.001; p-temp > 0.05), and all values stayed within normal clinical ranges.Conclusion: This work supports a fundamental idea in prophetic medicine and the foundation of lunar chronotherapy by offering the first empirical proof that mid-Hijri lunar days are linked to enhanced hemostatic and immunological responses. To verify their clinical usefulness after Hijama, more randomised controlled trials are required.